Basics productiondesign. 03, visual, conversation - Bramston, David (AVA, 2010)
introduces design students to the art of communication in product design. This title explains the process of translation from rough concept to fully-realised production. It emphasizes the importance of simplicity in creating effective sketches, and examines methods of eliciting an emotional response in the use of 2D and 3D mixed media.